ОХУ-АСЕАН-ы орнуудын улс төр, эдийн засгийн хамтын ажиллагаа - А, Нямдолжин (Journal of International Studies, 2009)
English title: Political and Economic cooperation of the Russian Federation and ASEAN Countries